Unchecked Powers of the Ethiopian National Intelligence and Security Service in the Prevention and Countering of Terrorist Crimes: Some Disquiets at a Glimpse - Belete, Shimels S. (European Scientific Journal, ESJ, 2018)
This article questions the supreme role of the Ethiopian National Intelligence and Security Service (NISS) in the prevention and countering of alleged terrorist acts vis-à-vis its institutional legitimacy and operational integrity. With no exception to other states, Ethiopia also re-established the National Intelligence and Security Service in 2013 but as a sole and unique institution of its kind with multiplex mandates both on general and specific intelligence and security matters. Having in mind the more sensitive powers conferred to the institution and its unrivalled authority in masterminding all the preventive and punitive measures against alleged terrorist conducts as enshrined under the Anti-Terrorism Proclamation of the country, this article examines whether the establishing proclamation has set the required normative standards and watchdogging institutional platforms to ensure its functional accountability. After investigating the Service’s organizational structure, the public, judicial and political watchdogging apparatuses, the lack of administrative and financial transparency, as well as the alleged alliance of the institution to the regime in power, this article submits that the Ethiopian National Intelligence and Security Service lacks the key attributes of a politically independent and functionally autonomous institution that strives to protect the nation’s politico-economic and security interests. As it stands, much of the Services’s mission rather appears to have been constricted to serving as an untouchable guardian of the party or the regime in power, or as a rising unique entity that roams on its own impervious orbit.